Quality improvement of rice-based gluten-free bread using different dietary fibre fractions of rice bran - Yuthana Phimolsiripol (2018)
Gluten-free (GF) breads are often characterised by low nutritional quality as they are mainly starch based and contain low amounts of vitamins, minerals and in particular dietary fibre. The objective of this study was to improve the physical, nutritional and sensory quality and shelf life of rice-based GF bread by adding different fractions of rice bran, containing different amounts of protein, fat, dietary fibre (DF) and different ratios of insoluble (IDF) to soluble (SDF) DF. As a first step, recipe parameters (content of HPMC, egg albumen and emulsifier) of GF bread with 10% rice bran addition were optimised. An amount of 3% HPMC, 1.5% emulsifier and 2% egg albumen provided acceptable structural and textural quality of GF bread. The main trials demonstrated that addition of rice bran, in particular when containing a high amount of SDF, produced better bread colour, higher specific volume, softer crumb firmness and improved porosity profile. All rice bran containing GF breads had higher protein and DF content and the ratio of IDF to SDF was improved substantially depending on the dietary fibre fraction of rice bran. Sensory acceptance was increased and shelf life extended, again when selecting a rice bran source with high SDF content. © 2012 Elsevier Ltd.